Does too much finance harm economic growth? - Law, Siong Hook; Singh, Nirvikar (Journal of Banking & Finance, 2014)
This study provides new evidence on the relationship between finance and economic growth using an innovative dynamic panel threshold technique. The sample consists of 87 developed and developing countries. The empirical results indicate that there is a threshold effect in the finance–growth relationship. In particular, we find that the level of financial development is beneficial to growth only up to a certain threshold; beyond the threshold level further development of finance tends to adversely affect growth. These findings reveal that more finance is not necessarily good for economic growth and highlight that an “optimal” level of financial development is more crucial in facilitating growth.